2001
DOI: 10.1079/bjn2001416
|View full text |Cite
|
Sign up to set email alerts
|

Increasing viscosity of the intestinal contents alters small intestinal structure and intestinal growth, and stimulates proliferation of enterotoxigenicEscherichia coliin newly-weaned pigs

Abstract: Sources of viscous soluble fibre, such as barley and oats, have often been included in the weaning diet of the pig to accelerate development of the large intestine. Inclusion of a non-fermentable, viscous compound, sodium carboxymethylcellulose (CMC), in a low-fibre weaning diet was tested to assess the influence of digesta viscosity on the gut in the absence of increased fermentation. Two CMC sources, of low and high viscosity, were added to cooked rice-based diet at 40 g/kg total diet. A third control rice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
2
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 52 publications
12
95
2
4
Order By: Relevance
“…Thus, the more soluble this feed fraction, the greater the viscosity (McDonald et al, 2001) and the lower the pH of the digesta , due to the fermentative potential of the fiber. The soluble fiber content of citrus pulp is high (31 %), which can justify the increase in viscosity of the digesta in the stomach and cecum at both 35 and 50 days of age, respectively.…”
Section: Sci Agric V72 N5 P400-410 September/october 2015mentioning
confidence: 99%
“…Thus, the more soluble this feed fraction, the greater the viscosity (McDonald et al, 2001) and the lower the pH of the digesta , due to the fermentative potential of the fiber. The soluble fiber content of citrus pulp is high (31 %), which can justify the increase in viscosity of the digesta in the stomach and cecum at both 35 and 50 days of age, respectively.…”
Section: Sci Agric V72 N5 P400-410 September/october 2015mentioning
confidence: 99%
“…Notable studies have demonstrated a direct effect of these compounds on mucosal barrier integrity, which translates to exacerbated intestinal inflammation or increased bacterial burdens in animal models. 17,18,27 Likewise, restrictive diets that eliminate processed foods are showing clinical Figure 3. Consumption of MDX decreases the mucosal barrier of the intestine and increases the proximity of commensal bacteria to the epithelial layer.…”
Section: Cultivating a Greater Understanding Of The Effect Of Diet Onmentioning
confidence: 99%
“…1). 16 Additionally, MDX consumption by preterm piglets lead to the expansion of ileal E. coli populations 17 and induced necrotizing enterocolitis in these animals, but not in fully developed pigs. 18 Increased levels of E. coli and AIEC strains have been repeatedly observed in ileal CD patients, suggesting a role for E. coli in disease pathogenesis.…”
Section: Maltodextrin (Mdx) Is a Common Food Additive That Alters Botmentioning
confidence: 99%
“…The samples were diluted 1:1 (v/v) with distilled water, mixed and centrifuged at 12 000g for 8 min. The viscosity of 0.5 ml supernatant fractions was measured at 258C, applying a shear rate of 60/sec (McDonald et al ., 2001). …”
Section: Methodsmentioning
confidence: 99%